Pengaruh Intensitas Penggunaan Smartphone Terhadap Etika Komunikasi Generasi Z: Studi Kasus Remaja Di Jorong Langgam Kecamatan Kinali - Ananda Emellya Agustanty; Syafwan Rozy (Lembaga Pengembangan Kinerja Dosen, 2023)
Information technology such as smartphones is a tool that can help human work in terms of searching for information, conveying information, processing data and many others. Technology has become a part of life for everyone nowadays. This study aims to determine the effect of the intensity of smartphone use on the communication ethics of the z generation (adolescents) in Jorong Langgam, Kinali District, West Pasaman Regency. By using two variables, namely variable X influencing variable Y. This research is included in associative research using quantitative data processing. The sample used in this study was 95 respondents from 1,800 adolescent populations in Jorong Langgam, Kinali District. Based on the results of the research that has been carried out, it can be found that there is a significant influence between variable X on variable Y. This is indicated by obtaining the value thutung = 12.375 > ttabel = 1.986 with sig probability of 0.000 < 0.05, according to the hypothesis that if thutung > ttabel then Ho is rejected and Ha ia accepted.